PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SD - Nelda Helvia; Atri Waldi; Reinita; Mansurdin (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research was motivated by the low learning outcomes of students in Pancasila education learning and in the learning process teachers did not use a variety of learning models. The aim of this research is to describe the improvement in student learning outcomes using the Problem Based Learning model in Pancasila education learning in class IV of SD Negeri 29 Batang Anai, Padang Pariaman Regency. This type of research is Classroom Action Research (PTK) which uses qualitative and quantitative approaches. Carried out in two cycles, cycle I consists of 2 meetings and cycle II consists of 1 meeting. The results of this research show an increase in: a) cycle I teaching modules with an average of 79% (C), cycle II with an average of 97.22% (A), b) implementation of teacher aspects of cycle I with an average of 82% (B), cycle II with an average of 96.42% (A), c) implementation of student aspects of cycle I with an average of 79% (C), cycle II with an average of 92.85% (A), and d) assessment of results student learning in cycle I with an average of 78% (C), cycle II with an average of 89% (B). It can be concluded that learning Pancasila education using the PBL model can improve the learning outcomes of class IV students at SD Negeri 29 Batang Anai, Padang Pariaman Regency